Estimation of Genetic Parameters for Production Traits Using Test-Day Random Regression Model in Holstein Friesian Crossbred Cattle - N Patel, Komal; M Patel, Pragnesh; C Patel, Ashish; G Nayee, Nilesh; S Joshi, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study was aimed to estimate genetic parameters for milk production traits in Holstein Friesian (HF) crossbred cattle using test-day  random regression models. A total of 1,59,950 first-lactation test-day milk yield records of 17,135 HF crossbred cows, sired by 259 bulls,  maintained in four districts of Gujarat (Panchmahal, Sabarkantha, Surat, and Tapi) between 1997 and 2019 were obtained from the  INAPH-MIS database of NDDB, Anand. Variance components, heritability, and repeatability were estimated using the Average Information  Restricted Maximum Likelihood (AI-REML) algorithm fitted with a Legendre polynomial function of days in milk. The average values for  test-day milk yield (TDMY), fat yield (TDFY), solid-not-fat yield (TDSNFY), and protein yield (TDPY) were 9.12, 0.38, 0.80, and 0.30 kg,  respectively. Heritability was moderate (0.24 for TDMY, 0.16 for TDFY, 0.22 for TDSNFY, and 0.17 for TDPY), with repeatability estimates  higher for TDMY (0.79) than other traits. Sire evaluation using univariate BLUP revealed average EBVs of 63.17 kg for 305-d milk yield, 1.69  kg for fat yield, 4.19 kg for SNF yield, and 1.39 kg for protein yield. The findings demonstrate the suitability of random regression test-day  models for genetic evaluation and highlight their potential utility in structured breeding programmes of HF crossbred cattle in Gujarat.
Keywords: Breeding value; Heritability; HF crossbred cattle; Random regression; Test-day model